Symmetric and Asymmetric Encryption Schemes for Internet of Things: A Survey - H. Shah, Nusrat; T. Khan, Durdana; A. Banu, Arshia; H. Shah, Lubna (International Journal of Intelligent Systems and Applications in Engineering, 2023)
IoT applications such as smart homes can monitor and control users' household chores anytime and anywhere. Similarly, Body Area Networks (BANs) can monitor the physical condition of a patient via various wearable sensors. Several authentication protocols have been proposed for embedded devices based on hash chains, symmetric cryptography, or PKC (public-key cryptography). Nevertheless, approaches based on hash chains and symmetric cryptography require storing large amounts of data regarding user identities and equivalent symmetric ECC keys with an increase in the number of devices. More seriously, updating a user's key and establishing a session key in such a protocol is a complex task. The various key authentication protocol for internet of things are reviewed in this paper. The major techniques which are already been proposed are focused on the complexity of the authentication model.